STUDENT SOLUTIONS MANUAL CALCULUS - Himonas Alex; Howard Alan (Wiley, 2003)
PRECALCULUS REVIEW LIMITS AND CONTINUITY EXPONENTIALS AND LOGARITHMS THE DERIVATIVE USING THE DERIVATIVE INTEGRATION FURTHER APPLICATIONS AND THE INTEGRAL
PRECALCULUS REVIEW LIMITS AND CONTINUITY EXPONENTIALS AND LOGARITHMS THE DERIVATIVE USING THE DERIVATIVE INTEGRATION FURTHER APPLICATIONS AND THE INTEGRAL